THE IMPACT OF PERCEIVED CORPORATE AFFINITY FOR TECHNOLOGY ON SERVICE OUTCOMES: A SIGNALING THEORY PERSPECTIVE. Issue 3 (3rd July 2018) - Fleming, David E.; Artis, Andrew B.; Harris, Eric G.; Solomon, Paul J.
Abstract : Congruity theory suggests that customers' attitudes toward technology limit the benefits service firms accrue from publicizing their technological relationship, but signaling theory suggests the opposite. Both are used to develop and test hypotheses regarding the relationships between customer perceptions of corporate affinity for technology (PCAFT) and service outcomes. The study reveals that there are differences between customer types. For traditional financial service customers, PCAFT is driven by customers' personal affinity for technology consistent with selective attention theory and PCAFT is positively related to service performance perceptions. For younger customers, personal affinity for technology moderates the link between PCAFT and service performance perceptions.